ASCVac-1, a Multi-Peptide Chimeric Vaccine, Protects Mice Against Ascaris suum Infection - Gazzinelli-Guimarães, Ana Clara; Nogueira, Denise Silva; Amorim, Chiara Cássia Oliveira; Oliveira, Fabrício Marcus Silva; Coqueiro-Dos-Santos, Anderson; Carvalho, Samuel Alexandre Pimenta; Kraemer, Lucas; Barbosa, Fernando Sérgio; Fraga, Vanessa Gomes; Santos, Flaviane Vieira; de Castro, Joseane Camilla; Russo, Remo Castro; et al. (Frontiers in Immunology, 2021)
Control of human ascariasis, the most prevalent neglected tropical disease globally affecting 450 million people, mostly relies on mass drug administration of anthelmintics. However, chemotherapy alone is not efficient due to the high re-infection rate for people who live in the endemic area. The development of a vaccine that reduces the intensity of infection and maintains lower morbidity should be the primary target for infection control. Previously, our group demonstrated that immunization with crude Ascaris antigens in mice induced an IgG-mediated protective response with significant worm reduction. Here, we aimed to develop a multipeptide chimera vaccine based on conserved B-cell epitopes predicted from 17 common helminth proteomes using a bioinformatics algorithm. More than 480 B-cell epitopes were identified that are conserved in all 17 helminths. The Ascaris-specific epitopes were selected based on their reactivity to the pooled sera of mice immunized with Ascaris crude antigens or infected three times with A. suum infective eggs. The top 35 peptides with the strongest reactivity to Ascaris immune serum were selected to construct a chimeric antigen connected in sequence based on conformation. This chimera, called ASCVac-1, was produced as a soluble recombinant protein in an Escherichia coli expression system and, formulated with MPLA, was used to immunize mice. Mice immunized with ASCVac-1/MPLA showed around 50% reduced larvae production in the lungs after being challenged with A. suum infective eggs, along with significantly reduced inflammation and lung tissue/function damage. The reduced parasite count and pathology in infected lungs were associated with strong Th2 immune responses characterized by the high titers of antigen-specific IgG and its subclasses (IgG1, IgG2a, and IgG3) in the sera and significantly increased IL-4, IL-5, IL-13 levels in lung tissues. The reduced IL-33 titers and stimulated eosinophils were also observed in lung tissues and may also contribute to the ASCVac-1-induced protection. Taken together, the preclinical trial with ASCVac-1 chimera in a mouse model demonstrated its significant vaccine efficacy associated with strong IgG-based Th2 responses, without IgE induction, thus reducing the risk of an allergic response. All results suggest that the multiepitope-based ASCVac-1 chimera is a promising vaccine candidate against Ascaris sp. infections.